1999
DOI: 10.1149/1.1390825
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Sol-Gel Formed Ir Metal Nanoparticles

Abstract: Electrochemical studies of a sol-gel (SG) derived Ir-containing film have shown conclusively that films formed by air drying or heating at temperatures below ca. 500°C are metallic in nature, exhibiting the typical signature of Ir metal. Both compact oxide formation and reduction, and the hydrogen adsorption and desorption underpotential deposited peaks are seen in cyclic voltammetry experiments in sulfuric acid solutions. The metallic nature of these films has also been confirmed by electron diffraction analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
7
25
0
Order By: Relevance
“…The formation of two phases is similar to what occurred during Ir nanoparticle formation, 18 where it was found that the Ir sol remained suspended in a black solution. In the present work, Au electrodes were coated with the solution phase, shown in this work to contain the suspended Pt nanoparticles.…”
Section: Resultssupporting
confidence: 68%
“…The formation of two phases is similar to what occurred during Ir nanoparticle formation, 18 where it was found that the Ir sol remained suspended in a black solution. In the present work, Au electrodes were coated with the solution phase, shown in this work to contain the suspended Pt nanoparticles.…”
Section: Resultssupporting
confidence: 68%
“…This can also be explained within the mechanism of Pickup and Birss as above. The same evolution with ceasing signal in this potential area was seen for a sol-gel film containing 2 nm metallic Ir nanoparticles 48 . Here a steady-state anodic charge was also developed after a certain number of cycles, which was in contrast to the oxidation of Ir metal wire studied for comparison 48 .…”
Section: Discussionsupporting
confidence: 67%
“…The same evolution with ceasing signal in this potential area was seen for a sol-gel film containing 2 nm metallic Ir nanoparticles 48 . Here a steady-state anodic charge was also developed after a certain number of cycles, which was in contrast to the oxidation of Ir metal wire studied for comparison 48 . For the Ir wire the mirror-image peak at 0.97 V continued to increase.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the successful use of NaOC 2 H 5 for Ir 22,23 and Ru oxide nanoparticle formation [34][35][36] and our interest in developing a one-pot synthesis of mixed noble metal nanoparticles supports our interest in further optimization of Pt nanoparticle formation using this reducing agent.…”
Section: Effect Of Reducing Agent To Pt Precursor Ratio On Pt Film Romentioning
confidence: 85%